The Effect of Covid- 19 on January Effect Events on Index Lq45 as the Basis of Investor Decision Making - Julio Julio; Nizwan Zukhri; Ari Agung Nugroho (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to determine the differences in stock prices, abnormal returns , and trading volume activity of the LQ45 Index in the January effect before the 2019-2020 COVID- 19 and the January effect during the 2021-2022 covid -19 event. This study uses a quantitative approach. The data collection technique used is the documentation method and the library method. The data source used is secondary data in the form of financial statements of companies listed in the LQ45 index stock on the IDX. The sampling technique used is purposive sampling with a total of 24 companies. The data analysis method used is the analysis of the average difference test with the observation period ( event window ) is 10 days at the beginning of the year opening in January. The results of this study indicate that there is no significant difference in stock prices and abnormal returns in the January effect event during the occurrence of covid -19, while in trading volume activity there is a significant difference in the January effect event and during the occurrence of covid -19. Keywords: January effect , Stock Price, Abnormal Return , Trading Volume Activity , LQ45.